Software engineering ontology - the instance knowledge (Part II) - Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S.; Sommerville, I. (Dr Sang H Lee, 2007)
Software engineering ontology provides software engineering concepts ? what they are, how they are related, and can be related to one another ? for representing and communicating over software engineering knowledge and project information through the internet. The ontology enables effective ways of sharing and reusing the knowledge and the project information for remote software engineers and software developers. Reaching a consensus of understanding is of benefit in a distributed multi-site software development environment. Software engineering knowledge is represented in the software engineering ontology whose instantiations are undergoing evolution. Software engineering ontology instantiations signify project information which is shared and has evolved to reflect project development, changes in software requirements or in the design process, to incorporate additional functionality to systems or to allow incremental improvement, etc. This evolution of instances provides many new challenges to an ability to design and deliver project information. In this paper, we present platforms development to facilitate software engineering ontology instantiations management.